THE INFLUENCE OF JOB EMBEDDEDNESS AND PERCEIVED ORGANIZATIONAL SUPPORT TOWARDS ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT KPKNL MANADO - Tumiwa, Deisye Gracelia; Pandowo, Merinda H. C. (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: In the work world of government institution today, the existing human resources are required to be more competent. Government institutions require employees to perform more than job descriptions or take good extra roles without pay. However, not all of employees or only some want to do or work an extra role without any payment. Thus, it becomes a problem and disadvantage if the employees do not want to self-giving for do the good action, it can disturb the organization to running well. This research has purpose to analyze the influence of job embeddedness and perceived organizational support towards organizational citizenship behavior. The sample of this research is 36 of KPKNL employees. Data analysis used Multiple Linear Regression analysis method conducted by using SPSS 25 version software with the saturation sampling as sampling technique. The results of this research show that Job Embeddedness and Perceived Organizational Support Influence Organizational Citizenship Behavior at KPKNL Manado simultaneously. Job Embeddedness has a positive relationship and has no significant influence towards Organizational Citizenship Behavior, while Perceived Organizational Support has a positive relationship and a significant influence towards Organizational Citizenship Behavior at KPKNL Manado.Â Keywords: job embeddedness, perceived organizational support, organizational citizenship behavior